Folic Acid Supplement Intake and Risk of Colorectal Cancer in Women; A Case Control Study - Sara Moazzen; Saeed Dastgiri; Roya Dolatkhah; Hossein Mashhadi Abdolahi; Behrooz Z. Alizadeh; Geertruida H. de Bock (Ubiquity Press, 2020)
Background: An ongoing controversy exists on the role of folic acid supplementation in colorectal cancer risk among epidemiological studies. Objective: To assess the association between maternal folic acid supplementation and colorectal cancer risk. Methods: A paired matched case control study of 405 subjects was performed, including women residing in 135 villages of East Azerbaijan, Iran. Per area, subjects were followed regularly in local healthcare centers, where health- and social-related information have been collected prospectively in face to face interviews by well-trained health workers. We extracted folic acid supplement intake, baseline characteristics, and confounders from healthcare records. The data for study participants were linked to national cancer registry repositories, from which we retrieved the data of 135 women diagnosed with colorectal cancer between 2005 to 2015. Two hundred seventy controls were individually matched with cases in terms of residing village, age, and gender. We applied multivariate conditional logistic regression to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Findings: There was no significant association between folic acid supplementation and colorectal cancer risk in those with history of folic acid intake compared to those with no history of intake (OR 0.95; 95% CI 0.59 to 1.53), in those with less than five years of folic acid (0.79; 0.45 to 1.39) or in those with ≥5 years intake (1.09; 0.52 to 2.26). This risk did not change after adjustment for covariates or further stratification. Conclusions: Maternal folic acid supplementation did not affect colorectal cancer risk in a population where supplemental folic acid is prescribed with regular intervals for women of child-bearing age.